Self-Rated Health among General Population in the West of Iran: A Cross-Sectional Analysis of Socioeconomic Determinants - Satar Rezaei; Ali Kazemi Karyani; Masoud Khosravipour; Farid Khosravi; Shahab Rezaeian (Epidemiology, Biostatistics and Public Health)
Background: This study aimed to investigate the relationship between self-rated health (SRH) and socioeconomic factors in the general population in the western Iran. Methods: A cross-sectional study was conducted in 2017 enrolling 1444 subjects aged 18 years and over in five areas of Kermanshah city. A single question of SRH with five scales of excellent (coded as 1), very good, good, fair, or poor (coded as 5) was used. Univariate and multiple logistic regression models were performed to determine factors associated with poor self-rated health. Results: The proportion of poor SRH was 14.2%. Multiple logistic regression showed that the most important determinants of poor SRH were older age (odds ratio(OR)31-50year=1.96, OR>51year=4.93, married status (OR=2.53), divorced or widowed status (OR=2.62), self-reported income level as middle (OR=2.51) and low (OR=4.59), rural residency (OR=1.5), low physical activity (OR=10.95) and having chronic diseases (OR=6.92). In addition, level of education had an inverse relationship with poor SRH (OR academic=0.47). Conclusion: Our results revealed that both individual and social factors are directly associated with poor SRH. Therefore, these determinant factors should be considered in health policies and planning for promoting health and SRH in the west of Iran.